Living and Dealing with Food in an Affluent Society—A Case for the Study of Lived (Non)Religion - Anna Sofia Salonen (Religions, 2018)
Significant changes have been taking place in the field of the sociology of religion in the last few decades, which challenge researchers to rethink this scholarly field. This article suggests that a great deal could be learned about the current dilemmas within this field through research that explores the moral underpinnings of everyday food consumption within contemporary society that is characterized by abundance. More specifically, the article proposes that everyday food consumption and everyday ethics provide unique opportunities to transcend and surpass crucial distinctions within social sciences in a way that can feed the sociological imagination in relation to research on lived (non)religion. Drawing on examples from research on food consumption in the nonreligious context and at the individual, discursive and institutional levels, this study shows how the everyday ethics of food consumption can serve as a point of departure for sociological research, which could help researchers to understand the currents of lived religion and nonreligion in a way that evades the idea of religion as a certain set of practices or beliefs, or as a specific religious affiliation. This research would enable the study of issues such as practices, beliefs, meanings and belonging, as well as distancing, withdrawal, and indifference.